Tindak Pidana Pencucian Uang - Husein, Yunus (UI Scholars Hub, 2021)
Money laundering is considered as a transnational organized crime. The logic of elimination money laundering is to omit the criminal’s motivation to enjoy their proceed of crime. The efforts to eliminate money laundering is much related to the issues of national jurisdiction. Thus, it requires international cooperation among countries, where international law is needed. Eventhough there is still no specific convention about money laundering, but regulation about money laundering is partially arranged in some conventions such as Vienna Convention 1988 and in UN Convention on Transnational Organized Crimes 2000. Indonesia has enacted a regulation is amended by UU No. 25 Tahun 2003. This article will describe the implementation of international law on money laundering in the list of non-cooperatives countries and territories (NCTT).